IMPLEMENTASI KEBIJAKAN MANAJEMEN PEGAWAI PEMERINTAH DENGAN PERJANJIAN KERJA - Harahap, Minati Fitriana; Dwi Fitria, Rima; Kusumaa , Muhammad Deni (Administratie: Jurnal Administrasi Publik, 2025)
The implementation of the Government Employees with Employment Agreement (PPPK) policy has become a crucial strategy in managing professional and flexible Civil Servants (ASN). This study aims to evaluate the effectiveness of the PPPK policy in Serang City using a qualitative method based on literature studies. Data were collected from academic literature, official documents, and thematic analysis related to the PPPK policy. The results indicate that transparent communication, technological utilization, and effective bureaucratic coordination significantly contribute to the success of this policy. However, challenges such as unfilled positions due to a lack of qualified applicants remain a major obstacle. In conclusion, the PPPK policy in Serang City has achieved significant progress in many aspects but requires strengthened coordination and communication strategies to overcome existing challenges.